EKSPLORASI JENIS ROTAN DI KABUPATEN TIMOR TENGAH SELATAN, PROVINSI NUSA TENGGARA TIMUR - Titi Kalima; Jamaludin Malik; Sunarto Sunarto (Jurnal Pro-Life, 2019)
South-Central Timor District with the area of ​​3,955.36 km2 holds a lot of diversity of non-timber forest products, including rattan plants. Rattan is widely spread in forest area which is its natural habitat. The increasing of both legal and illegal forest exploitation and land conversion resulted in the habitat damage. Some communities around the forest have used rattan as raw material for plaits, ropes and household needs, while the rattan has not been inventoried and cultivated properly. The purpose of this study is to determine the diversity of rattan species and utilization by the people in the District of South-Central Timor, East Nusa Tenggara Province. Field research activities were carried out using the exploration method in the Kualeui forest area, namely the villages of Oelalali, Sub-District of Kualin and Lolli Village, Sub-District of Pollen. Rattan data collection was recorded in passport data followed by data documentation. Exploration results show that the forests of South-Central Timor Regency found three species of rattan consisting of two genera, namely Calamus and Daemonorops. In this district, rattan grows at the altitude of 100-1500 above sea level. The most commonly used rattan species by communities around the forest are Calamus timorensis Beccari and C. toli-toliensis Beccari ex Heyne, while Daemonorops melanochaetes Blume is not utilized. Therefore there is a need for further development of the utilised rattan. Keywords: Exploration, Rattan, South-Central Timor District, Utilization.